Diametric growth model of Nothofagus alpina and its relationship with that of Nothofagus obliqua and Nothofagus dombeyi in the natural forest from Patagonia of Argentina - Attis Beltrán, Hernán; Chauchard, Luis; Dezzotti, Alejandro; Martínez Pastur, Guillermo (BOSQUE, 2018)
Tree growth models contribute to describing the structure and functioning of forests, predicting timber production, implementing appropriate silvicultural practices and assessing the economic dimension of forestry. Nothofagus alpina, Nothofagus obliqua and Nothofagus dombeyi (Nothofagaceae) form natural forests in Northwestern Patagonia of Argentina. Models of diametric increment and yield were developed for N. alpina trees from the intermediate and superior canopy strata, through Bertalanffy - Richards’s functions. They were interpreted together with those for N. obliqua and N. dombeyi, formerly developed using the same methodology. In all three species, intermediate trees exhibited the lowest diametric growth, probably in response to differences in the amount and composition of light. Growth of N. alpina trees, compared to N. dombeyi, was similar for all age classes within the intermediate stratum, and lower for older classes within the superior stratum. However, the performance of this species was adequate in both strata, which would be associated with the superior shade tolerance (perceived in the intermediate stratum) and the response to increasing light (in the upper one). Nothofagus obliqua experienced the slowest growth for all social strata and age classes. Discrepancies observed among models were compatible with interspecific differences in intrinsic growth and demand of light. The simultaneous interpretation of growth models of N. alpina, N. obliqua and N. dombeyi can contribute to deeply understand ecological patterns and processes of this subantarctic forest, aimed at its conservation and sustainable management.